New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species - Szadziewski, Ryszard; Gwizdalska-Kentzer, Marta (Zootaxa, 2020)
Biting midges (Ceratopogonidae) are a relatively well-studied family of nematocerous flies (Borkent & Dominiak 2020), but the ceratopogonid fauna of the Middle East is not well known. To date, only 264 species from this family have been recorded in this entire region (Alwin et al. 2016a, b) and just 53 in the United Arab Emirates (UAE) (Szadziewski et al. 2011, Alwin et al. 2016a, b). Here, we report on three species of biting midges new to the fauna of the UAE.